Structure and tree diversity of an inland Atlantic Forest–A case study of Ponte Branca Forest Remnant, Brazil - Antonio Tommaselli; Nilton Imai; Adilson Berveglieri; Mariana Thomaz; Gabriela Miyoshi; Baltazar Casagrande; Raul Guimarães; Eduardo Ribeiro; Eija Honkavaara; Mariana Campos; Raquel de Oliveira; Hassan David; Rorai Martins-Neto (Indonesian Journal of Geography, 2022)
The Atlantic Forest is the most fragmented and threatened domain in Brazil. The main remnants are in the coastal regions. This paper describes a study performed at a protected federal reserve in Brazil located in western of São Paulo state, which is a transition with the Savannah. A forestry survey was made for understanding the forest structure, diversity, and floristic composition of an inland Atlantic Forest area. A total of 3,181 individuals with a Diameter at Breast Height over 3.5 cm were sampled. The data sample was composed of 29 families and 64 species from 15 plots. Forty-seven percent of the species were classified as a pioneer, 42% as secondary, and 11% as climax. The species Eugenia uniflora presented the highest importance value index. The values of Shannon-Weaver diversity and Pielou equitability index indicate the area has less diversity than others in the same phytophysiognomy and was dominated by a few species with many individuals. Several anthropogenic disturbances altered the forest cover of the Ponte Branca Forest remnant, which is in the process of secondary succession.